2017
DOI: 10.1111/jace.15301
|View full text |Cite
|
Sign up to set email alerts
|

Ultralight and resilient Al2O3 nanotube aerogels with low thermal conductivity

Abstract: This report describes a novel method to produce fluffy and resilient nanotube aerogels by combining solution blow spinning and Atom Layer Deposition (ALD). Polyvinylpyrrolidone (PVP) sponges obtained by blow spinning are used as templates and are deposited in ALD. After removal of template, semitransparent aerogels whose density can be as low as 0.68 mg/cm 3 were obtained. The product is heat-stable, with the ability to retain original shape and keep elastic after being kept at 900°C for 2 hours. It is also he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 41 publications
0
45
0
Order By: Relevance
“…n recent years, various sponge-like materials, including carbon nanotube aerogels 1,2 , biomass-derived aerogels [3][4][5][6] , graphene aerogels [7][8][9][10][11][12] , ceramic nanofiber aerogels [13][14][15] , and carbon nanofiber aerogels [16][17][18] , have received significant interest owing to their high compressibility and resilience under large deformation, which results from their porous three-dimensional network structures. Among them, ceramic sponge materials have attracted more interest owing to their lightweight feature, high specific surface area, low thermal conductivity, and excellent chemical and thermal stability 13,14,19,20 .…”
mentioning
confidence: 99%
“…n recent years, various sponge-like materials, including carbon nanotube aerogels 1,2 , biomass-derived aerogels [3][4][5][6] , graphene aerogels [7][8][9][10][11][12] , ceramic nanofiber aerogels [13][14][15] , and carbon nanofiber aerogels [16][17][18] , have received significant interest owing to their high compressibility and resilience under large deformation, which results from their porous three-dimensional network structures. Among them, ceramic sponge materials have attracted more interest owing to their lightweight feature, high specific surface area, low thermal conductivity, and excellent chemical and thermal stability 13,14,19,20 .…”
mentioning
confidence: 99%
“…Alumina (Al 2 O 3 ) is extensively used in lightweight refractories 6,7 and structural elements 8 for the modication of polymers, 9 batteries, 10 and so forth. Similarly, zirconia (ZrO 2 ) possesses a relatively low thermal conductivity, a high melting point, 11 and high temperature strength, 7 thereby leading to its signicant potential in thermal applications. 11,12 In many cases, composite materials with certain structures show properties beyond those of single compositions.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Using solution blow spinning and atomic layer deposition (ALD), Xu et al produced novel Al 2 O 3 nanotube aerogels having a pore size of 1-2 mm, whose thermal conductivity is only 0.022 W m À1 K À1 at room temperature. 7 Nevertheless, few studies have reported the thermal performance of Al 2 O 3 -ZrO 2 composites at a high temperature (900-1600 C) till now. In addition, there are some universal problems in ceramic preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional TE materials based on bismuth and tellurium, CNT‐based composites advanced in flexible, while the output electric power is still too low. The CNT‐based composites only have a ZT of about 10 −5 to 10 −6 magnitude . It is still very promising to further enhance the performance of the CNT composites.…”
mentioning
confidence: 99%
“…The CNT-based composites only have a ZT of about 10 −5 to 10 −6 magnitude. 26,27 It is still very promising to further enhance the performance of the CNT composites. The three-dimensional sponges synthesized by packing the CNTs or nanowires into bulk may have an even better TE performances.…”
mentioning
confidence: 99%